The Implementation of Discovery learning Assisted with Manipulative Teaching Tools on The Mathematical Understanding Concept of Students (Journal of Primary Education, 2019)
This study has a purpose of examining the differences in the improvement of the mathematical understanding concepts of students between the class using discovery learning assisted with manipulative teaching tools compared to the class using discovery learning without the manipulative teaching tools. This study was a quasi-experimental design study. The sampling technique was applied in this study is the purposive sampling technique, a sampling technique which conducted using certain considerations. Therefore, the samples were obtained Public Elementary School Dukuh 05 Salatiga as the experimental class and Public Elementary School Dukuh 01 Salatiga as the control class with a total of 54 students for each class. The data collection techniques in this study were used test of mathematical understanding concepts. The results showed that there was a difference in the improvement of the mathematical understanding concepts in the experimental class using the discovery of learning assisted with manipulative teaching tools. This is indicated by N-Gain score in the experimental class at 0.55, whereas, the control class at 0.29. This result is supported by the independent sample t-test, which shows that the sig. (2-tailed) is 0.000 < 0.05. The mathematical understanding concepts in the class using the discovery of learning assisted with manipulative teaching tools is higher. The implementation of the discovery learning assisted with manipulative teaching tools can be used as a solution for teachers in improving the mathematical understanding concepts of students.